Gravity modeling of the lithosphere in the Calatrava Volcanic Province (Spain): geodynamic implications. - Granja Bruña, José Luis; Vargas, R.; Sentre Domingo, M.A.; Muñoz-Martín, A.; Sainz-Maza Aparicio, S. (Journal of Iberian Geology, 2015)
The origin of the intraplate volcanism in the Calatrava Volcanic Province (CVP) is controversial. On the basis of its geochemical signature it has been ascribed to an “aborted” rift, implying lithospheric thinning. However, the volcanism occurred during the generalized Cenozoic NW−SE-oriented compressive tectonic regime. On the other hand, on the basis of evidence for its deep-seated origin, it has been linked to the existence of a baby-plume detached from an active megaplume below the Canary-Azores Islands and the western Mediterranean. In order to understand better the aforementioned geodynamic scenarios for the origin of the CVP, we address here the study of the lithosphere in the CVP and its vicinity by means of gravity analysis and 2+1/2D modeling. Gravity modeling results do not support the rifting model adopted for the intraplate volcanism occurred in the CVP because the crust shows a constant thickness. Density models suggest the existence of a sub-crustal, anomalous low-density block that could be underplated magmatic material at the base of the crust, suggesting that only a minor part of it intruded up into the crust and erupted. The localized magmatism of the CVP can be related to the combination of two factors: one active, the gentle folding of the Iberian lithosphere and associated uplifting of the Variscan basement due to the NW-directed transmission of compressive stresses in the upper plate yielded by the subduction/collision in the south Iberian margin. The formation of the lithospheric folding in the Calatrava region results in a decrease of the pressure beneath the swell of the antiform that is likely to bring about basaltic magmatism below the swell; and one passive, the existence of a Variscan right-lateral shear band, which yields a weakened crust that facilitates the ascent of the magmatic materials. The relatively small volume, but large extension, of the volcanic outcrops could be associated with the preferential ascent of the magmas along the weakened crust of this NW−SE-trending Variscan shear band.